Outcome of type and screen versus crossmatch in cardiovascular surgery patients: A comparative study - Anupa Pokhrel; Ashish Jain; Neelam Marwaha; Rana Sandip Singh (Asian Journal of Transfusion Science, 2022)
BACKGROUND: The need for an anti-human globulin (AHG) cross-match (XM) when the antibody screen (ABS) is negative is debatable and a matter of policy. AIM: (1) To compare the outcomes of type and screen (T and S) method versus the AHG-XM in terms of posttransfusion alloimmunization and hemolytic reactions. (2) Calculation of XM transfusion ratio in both groups. MATERIALS AND METHODS: The study included 200 patients undergoing elective cardiovascular surgery. Group I patients (n = 100) were issued packed red blood cell units after ABO and RhD typing, an ABS followed by an immediate spin XM (T and S protocol), while Group II (n = 100) patients by an AHG-XM. In Group II patients, if incompatibility was found, then an ABS and identification were performed. A posttransfusion ABS and a direct antiglobulin test (DAT) was done on the 4th day. The XM, ABS (3-cell panel) and DAT were done using the gel technique (Bio-Rad, Switzerland). Thus, the outcomes of T and S method versus the AHG-XM in terms of posttransfusion alloimmunization and hemolytic reactions was measured. The XM transfusion ratio was also calculated in both groups. RESULTS: In each of Groups I and II, 99 patients (99%) were transfused. There was no significant difference between the two groups based on previous transfusion (P = 0.621) or combined history of transfusion and pregnancy (P = 1). In Group I, all the patients were negative for ABS. In Group II, an AHG-XM was incompatible for 1 patient (1%) due to anti-c and anti-E alloantibodies and had a history of pregnancy as well as transfusion. In both the groups, none of the patients had any adverse transfusion reaction and the posttransfusion ABS and DAT were negative. CONCLUSION: ABS is a better tool than AHG-XM in detecting alloantibodies in patients having the previous history of transfusion and/or pregnancy.